1916 N.J. Laws 275-76, ch. 130, §§ 1-2 - (:unkn) unknown (General Publisher, 1916)
Prohibited any individuals from going into the woods or fields with a firearm while intoxicated or under influence of drugs or alcohol. Punishable by revocation of hunting and fishing license.
--
Keywords: HUNTING REGULATION